2017
DOI: 10.7774/cevr.2017.6.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and compensation claims for adverse events following immunization from 2011 to 2016 in the Republic of Korea

Abstract: PurposeIn recent years, research on reported adverse events following immunization (AEFI) and claims filed for compensation has been lacking. We reviewed reported AEFIs and compensation claims in Korea from 2011 to 2016.Materials and MethodsWe listed all of the AEFI registered in the Integrated Management System of Disease and Public Health and reviewed the list of claims filed and serious AEFIs reported from 2011 to 2016.ResultsAn average of 278 AEFI cases was reported annually from 2011 to 2016. Of these, 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(20 reference statements)
2
9
2
Order By: Relevance
“…34 A study conducted in the Republic of Korea has identified an annual average of 278 cases of AEFI. 35 These data corroborate the responsibility of the professionals who deal daily with the administration of the immunobiological agents, since errors of conservation, handling and application of the immunobiological can result in AEFI.…”
Section: Vaccination In Everyday Life and Permanent Educationsupporting
confidence: 64%
“…34 A study conducted in the Republic of Korea has identified an annual average of 278 cases of AEFI. 35 These data corroborate the responsibility of the professionals who deal daily with the administration of the immunobiological agents, since errors of conservation, handling and application of the immunobiological can result in AEFI.…”
Section: Vaccination In Everyday Life and Permanent Educationsupporting
confidence: 64%
“…20 Additionally, the South Korean government operates a routine compensation system for AEs and has been providing compensation for 95% of the claims regarding BCG. 21,22 In our study, the Japanese encephalitis vaccine showed an association with allergic reactions, most of which were hypersensitivity reactions and urticaria. Allergic reactions to the Japanese encephalitis vaccine, including urticaria, anaphylaxis, and angioedema, have been reported in several studies.…”
Section: Discussionmentioning
confidence: 49%
“… 20 Additionally, the South Korean government operates a routine compensation system for AEs and has been providing compensation for 95% of the claims regarding BCG. 21 22 …”
Section: Discussionmentioning
confidence: 99%
“…The report of AEFI in Korea has continued since 1994 and it has been dualized to the Korea Institute of Drug Safety and the KCDC to monitor the adverse events (2012) [ 7 ]. The most frequently reported cases of AEFI of KCDC is BCG, which is more than 20% of all reported cases each year [ 8 ]. Very few previous studies have reviewed the reported adverse event after BCG vaccination.…”
Section: Discussionmentioning
confidence: 99%